Spigelian hernia - Rajbhandari, Ashish; Shrestha, ML (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Spigelian hernia is a rare ventral hernia which occurs due to defect / weakness in the spigelian fascia. They are difficult to diagnose and have vague symptoms. We report a 62 year male who presented with a left lower abdominal lump after a fall. A diagnosis of left spigelian hernia was made after clinical examination and confirmed by ultrasound. He underwent mesh repair and had an uneventful post operative period.